Visual Inspection and Non-Destructive Test (NDT) on ASTM A36 Welded Joints Produced by GMAW - Darsono, Febri Budi; Nurdin, Akhmad; Titio Koin, Sudibtia; Kaleb Thomas, Alvreando; Mulyono, Tasih; Setiyawan, Andri; Huda, Khoirul; Fajar Fitriyana, Deni; Doni Widodo, Rahmat; Rusiyanto, Rusiyanto (International Journal of Integrated Engineering, 2024)
Low-carbon steel is often used for welding joints, whether in the form of structural steel or other materials; the application of this material is used in shipbuilding, bridge construction, and other fields. Welding inspection is needed to determine the quality of the weld. Visual inspection and non-destructive testing (NDT) are techniques in welding inspection. This study aims to determine the results of visual inspection and non-destructive testing (NDT) on welding joints of low-carbon steel produced by GMAW. The welding joints used are V-butt joints with a bevel angle of 300, 10 mm thick plate, 2.6 mm root gap, variations in welding layers: 3 layers (root pass, filler pass, and capping), and 4 layers (root pass, 2 filler passes, and capping), filler metal ER 70S-6 0.8 mm, and CO2. Volts, current, travel distance, and shielding gas flow rate are welding parameters. The tests carried out were visual inspection referring to limits for imperfections in ISO 6520-1, non-destructive tests (NDT) that were carried out, namely penetrant tests and radiography tests. The visual inspection and non-destructive testing (NDT) on specimen 1 reveal an internal defect, specifically a lack of fusion; the specimen should be rejected. Specimen 2 shows an imperfection in the surface area, namely in the form of spatter (2 spots), and there are internal imperfections in the form of porosities with an area of less than 3%. The specimen should be accepted.